The impact of population aging and fertility rate on economic growth in Malaysia - Abdul Karim, Zulkefly; Nuruddin, Nurul Aqilah Mohd; Abdul Karim, Bakri; Mohamad, Massita; Ishak, Ismahalil (Economic Journal of Emerging Markets, 2023)
Purpose ― This study aims to examine the impact of population aging and fertility rates on economic growth in Malaysia for the sample spanning from 1961 to 2020.Method ― The study uses an Autoregressive Distributed Lagged (ARDL) model to examine the relationship between economic growth, the aging population, fertility rate, capital stock, and employment rate.Findings ― The main results provide evidence of a long-run relationship between aging, fertility rate, employment, and capital stock on Malaysian economic growth. The results also show that the aging population harms economic growth in the long run, but a decline in the fertility rate has been favorable to long-term economic growth.Implication ― These findings have significant implications for the execution and formulation of national aging and demographic policies and government efforts to achieve long-term fiscal sustainability.Originality ― This study empirically investigated the link between population aging and economic development, reflecting recent demographic trends in Malaysia. This study uses current data and an Autoregressive Distributed Lagged (ARDL) technique to analyze long-term economic growth and its association with supply-side determinants